2014
DOI: 10.1175/jcli-d-13-00450.1
|View full text |Cite
|
Sign up to set email alerts
|

Millennial Variability in an Idealized Ocean Model: Predicting the AMOC Regime Shifts

Abstract: A salient feature of paleorecords of the last glacial interval in the North Atlantic is pronounced millennial variability, commonly known as Dansgaard-Oeschger events. It is believed that these events are related to variations in the Atlantic meridional overturning circulation and heat transport. Here, the authors formulate a new low-order model, based on the Howard-Malkus loop representation of ocean circulation, capable of reproducing millennial variability and its chaotic dynamics realistically. It is shown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 67 publications
1
14
0
Order By: Relevance
“…Unlike previous studies which aimed at predicting the AMOC variability (Hawkins and Sutton 2009;Robson et al 2012aRobson et al , 2014Sévellec and Fedorov 2014), we assume in this paper that we know the AMOC, and want to know what we can predict from this starting point.…”
Section: Methodsmentioning
confidence: 99%
“…Unlike previous studies which aimed at predicting the AMOC variability (Hawkins and Sutton 2009;Robson et al 2012aRobson et al , 2014Sévellec and Fedorov 2014), we assume in this paper that we know the AMOC, and want to know what we can predict from this starting point.…”
Section: Methodsmentioning
confidence: 99%
“…However, the magnitude (a few Sverdrups) and typical periodicity (decadal to centennial) of such variations mismatch the observed millennial variability during the past glacial‐interglacial interval. In contrast, a possibility of pronounced self‐sustained oscillations on a millennial timescale has been shown by many models of lower complexity, from box models (e.g., Colin de Verdière, ; Colin de Verdière et al, ) and loop models (mapping the ocean overturning circulation onto a rotating wheel; e.g., Sévellec & Fedorov, , ; Winton & Sarachik, ) to simplified coupled models (e.g., Sakai & Peltier, ; , ; Weaver & Hughes, ; Weijer & Dijkstra, ), suggesting that one or more of AMOC steady states may be unstable. This appears to be especially true for the models configured for glacial conditions.…”
Section: Implications Of the Amoc Stability Paradigm For The Past CLImentioning
confidence: 99%
“…This appears to be especially true for the models configured for glacial conditions. A plausible change in the AMOC behavior from the present-day climate to glacial conditions can be illustrated by a simple loop model of the AMOC (Sévellec & Fedorov, 2014, 2015Figure 9). The model assumes that the overturning circulation can be represented as a simple rotation on a latitude-depth plane and the flow is driven by a buoyancy torque balanced by friction.…”
Section: Intrinsically Generated Millennial Variabilitymentioning
confidence: 99%
“…In this new model, the chaotic dynamics are generated internally by nonlinearities of the system. The model is a modification of the Howard-Malkus loop (Howard, 1971;Malkus, 1972;Welander, 1957Welander, , 1965Welander, , 1967, analogous to the waterwheel model (Dewar & Huang, 1995Strogatz, 1994), and representing AMOC dynamics (Sévellec & Fedorov, 2014. This model reads:…”
Section: Deterministic Frameworkmentioning
confidence: 99%
“…Hence, detection of early warning signals (Dakos et al, 2008;Lenton, 2011;Livina & Lenton, 2007;Scheffer et al, 2009) of an AMOC abrupt shutdown has become an extensive and fruitful area of current research. The research aims to determine precursors through statistical (Cimatoribus et al, 2013) or dynamical (Sévellec & Fedorov, 2014) approaches that assess the proximity of a dramatic AMOC event. In particular, it has been suggested that, whereas statistical early warning signals are weak (Cimatoribus et al, 2013), the ocean vertical stratification can be a good precursor of a dramatic collapse of the AMOC (Sévellec & Fedorov, 2014).…”
Section: Contributing Factorsmentioning
confidence: 99%